Institutional climate and evaluation of educational quality at IE Sagrada Familia APOVA. Ancon. Lima - Salvatierra Medina, Sebastiana (2023)
The relevance of carrying out a study on the relationship between the institutional climate and the evaluation of educational quality is becoming a necessity, given the poor results in ECE tests of public school students in Peru, especially in EI. The Holy Family in Ancón, Lima. . It is not unknown that teamwork, intra and interpersonal relationships, dialogue, empathy and more are relevant. Through a quantitative approach, hypothetical deductive method, an ordinal, cross-sectional level, with a correlational design using two questionnaires with 20 indicators validated by three expert juries and a reliability measure with Cronbach's alpha coefficient, to collect the information and a sample of 34 teachers we reached conclusions regarding this relationship. The data analysis is carried out through descriptive and inferential statistics for the hypothesis test, giving as a result that there is a significant relationship between the two variables in question, in that teachers have a deficient level regarding their educational quality, so important. for a good institutional climate on which ultimately depend the quality of the services that EI offers.